COST EFFICIENCY LEVEL OF RURAL BANKS IN EAST JAVA - Mongid, Abdul; Notodihardjo, Fx Soegeng (UNIVERSITY OF MERDEKA MALANG, 2009)
Abstract: Rural Bank (BPR) was an important part of financial service industry in Indonesia.Their pivotal role on lending to SMEs in the rural area made their existence very strategic torural development. However, due to its operational scale, rural bank charged higher interestrate than commercial bank. The study estimated the cost efficiency of rural banks usingparametric approach. The result found that rural bank efficiency was very high. The two yearcost efficiency estimated using frontier 4.1 was 95% and median was 100%. The lowest of costefficiency level was 32%. It meant cost inefficiency of the banks under investigated was around10%. The cost efficiency level in 2006 was on average 95% and the median was 100%. It meantthat 50% or more of the observation enjoyed 100% cost efficiency. The minimum was only67%. It meant they operated at very efficient level, leaving only 5% inefficiency. In 2007, adramatic change on efficiency level was going on. The average efficiency was dropped from11% to 89.9% due to increase on interest rate and price level.